Superior-Labrum Anterior-Posterior Return to Sport Index (SLAP-RSI) Score to Quantify Psychological Readiness to Return to Play (223). Issue 10 (31st October 2021) - Colasanti, Christopher; Hurley, Eoghan; Lorentz, Nathan; Markus, Danielle; Matache, Bogdan; Campbell, Kirk; Jazrawi, Laith; Strauss, Eric
Objectives: Superior-labrum anterior-posterior( SLAP) tears are common among athletic populations and may require surgical treatment. Return to play post-operatively may be complicated by a number of factors, including psychological readiness to return. The purpose of this study was to evaluate the use of the SLAP Return to Sport Index (SLAP-RSI) score to quantify psychological readiness to return to play following operative management of SLAP tears. Methods: A retrospective review of athletes who underwent operative management of SLAP tears with a minimum of 12-month follow-up was performed. Patients were evaluated for their psychological readiness to return to sport using the SLAP-RSI score. The SLAP-RSI score was created by adapting the terms in the Anterior (ACL-RSI score) with terms related to SLAP tears. A SLAP-RSI score > 56 is considered a passing score for being psychologically ready to return to play. Results: The study included 174 athletes who underwent operative management of SLAP tears. Overall, 73.5% percent of patients were able to return to play, and the mean SLAP-RSI score in this cohort was 74.1±20.9, as compared to 46.7±27.7 in those who were unable to return (p<0.0001). Of those who returned, 82.1% passed the SLAP-RSI benchmark of 56, while of those who did not return, 33.3% passed the SLAP-RSI benchmark of 56. Additionally, a significant difference was found in each component of the SLAP-RSI score between the two cohorts (p<0.05). No individual component of the SLAP-RSI score was below 56 in patients who were able to return to play, while none was above 56 in those who were unable to return. Among patients who were unable to return, ones who cited lifestyle reasons had a higher SLAP-RSI score (77.4 ± 21.8) than those who cited residual pain (28.2 ± 15.1) or fear of re-injury (42.6 ± 23.6) (p<0.0001). Conclusions: Following the operative management of SLAP repair, patients that are unable to return to play exhibit poor psychological readiness to return which may be due to residual pain or fear of re-injury.